2022
DOI: 10.1101/gr.276521.121
|View full text |Cite
|
Sign up to set email alerts
|

Precision environmental health monitoring by longitudinal exposome and multi-omics profiling

Abstract: Conventional environmental health studies have primarily focused on limited environmental stressors at the population level, which lacks the power to dissect the complexity and heterogeneity of individualized environmental exposures. Here, as a pilot case study, we integrated deep-profiled longitudinal personal exposome and internal multi-omics to systematically investigate how the exposome shapes a single individual's phenome. We annotated thousands of chemical and biological components in the personal exposo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 74 publications
1
31
0
Order By: Relevance
“…">A multidimensional and interdisciplinary approach is needed to investigate how external environmental exposures are translated into internal exposures and responses, disturbing molecular interactions at the DNA, RNA, protein, and metabolite levels, leading to corresponding health outcomes. A recent study attempted to integrate the personal external and internal exposome and investigated the health outcome of individuals using multiomics [24]. The recent decade's translational achievements of microbiome research set an excellent example for this goal. …”
Section: Outstanding Challengesmentioning
confidence: 99%
“…">A multidimensional and interdisciplinary approach is needed to investigate how external environmental exposures are translated into internal exposures and responses, disturbing molecular interactions at the DNA, RNA, protein, and metabolite levels, leading to corresponding health outcomes. A recent study attempted to integrate the personal external and internal exposome and investigated the health outcome of individuals using multiomics [24]. The recent decade's translational achievements of microbiome research set an excellent example for this goal. …”
Section: Outstanding Challengesmentioning
confidence: 99%
“…An increasing number of personal sensors are being developed to monitor heart rate, blood sugar concentrations, blood pressure, muscle activity, temperature, and sweat production [98]. Remarkable advances in novel algorithms in wearable technologies are allowing for accurate acquisition of personal temperature exposures, chemical and biological exposures, and clinical laboratory measurements to explore individual-level 24-h exposures in various microenvironments in exposome studies [99][100][101][102]. Koelmel et al captured the changes in gas-and particulate-phase airborne chemicals to which individuals were exposed and determined which exposures posed the greatest risk to health.…”
Section: Individual-level Exposures Portable/personal Sampling and Se...mentioning
confidence: 99%
“…Next-generation sequencing and liquid chromatography‒mass spectrometry (LC‒MS) technologies were then used to detect the biotic/chemical exposome and found that the human exposome was dynamic and influenced by various environmental and spatial/lifestyle variables. Gao et al examined the effects of environmental exposures on well-dissected personal internal health changes based on longitudinal individual exposomes and internal multiomics (gut microbiome, proteome and metabolome) [ 101 ]. By investigating the correlations of exposomics and the exposome and clinical data, it was found that changes in external exposures could be associated with thousands of biomolecular changes in the body involved in immune, kidney, and liver functions.…”
Section: Exposomic Measurement Tools For Use In Age-related Disease S...mentioning
confidence: 99%
“…Altogether, these data emphasized that environmental diseases are a crucial issue in the current literature, with growing attention to the international policies targeting environmental modification to improve global health [ 2 ]. In this scenario, several environmental factors might be associated with human health and might be effectively targeted by precise environmental strategies [ 19 ]. However, environmental modifications might have a crucial impact not only on global health but also on functional impairment.…”
Section: Environmental Diseasesmentioning
confidence: 99%